Disentangling Exploitation and Exploration in Hybrid Projects: The Case of a New Nuclear Reactor Development. Issue 5 (October 2019) - Tillement, Stéphanie; Garcias, Frédéric; Minguet, Guy; Duboc, Florence Charue
Using a qualitative research approach, this article addresses a gap in the project management literature that is the coexistence of exploitation and exploration learning dynamics within a single large-scale and complex project. We investigate the case of the New Sodium Fast Reactor (NewSFR) project, a large-scale, complex, and multi-actor project aimed at designing a new technology of nuclear reactor. Through a grounded, interpretive, and multilevel methodological approach, we characterize NewSFR as a hybrid project that combines high exploration and exploitation goals. We investigate the hybridizing process, which takes into account long-term temporal dynamics and interactions between two levels of analysis: the knowledge domains within the project and the project itself. This enables us to report three major contributions. First, at a macro-level, we highlight the ambiguity related to the difficulty for project members to agree on either exploratory or exploitative NewSFR status, which leads us to qualify it as a hybrid project. We then investigate the case dynamically and at a micro-level (i.e., the level of knowledge domains within the project). We emphasize the temporal processes underlying the hybridization, and how this hybridization evolves in time through two data-based concepts: deliberate exploration and emerging exploration. We identify and categorize the main drivers of deliberate and emerging exploration throughout the project, and highlight how these drivers affect project management processes. Finally, we discuss the issue of managing such hybrid projects.